Eternal Recurrence of (almost) the Same. Nostalgia in Italian Advertising from Carmencita and Gringo to Jake la Furia - Migliorati, Lorenzo (Italian Sociological Review, 2014)
The paper sets out to analyse the relationship between past, present, and future as applied to the behaviour of consumption. The favoured approach examines the use of nostalgia in advertising and in several forms of Italian contemporary national popular culture. The hypothesis posits that the emotion of nostalgia acts as a powerful factor in mobilising consumers because it inspires a desire that can speak not only to the past (which is impossible to recover) but also to the future; the latter here is taken as what one could achieve via a consumption which employs the past as a symbolic resource to activate desire. The study delineates three main strategies via which communication makes efficient use of nostalgia: the special dynamic of drawing the subject and object closer together and farther apart, the past’s identity-related function, and the memory’s complex work of interpretation and reconstruction of the past. The text will examine some specific examples of advertising commercials and mass-media products which demonstrate the emotion of nostalgia’s capacity to mobilise consumers.